The Role of social and cultural factors in consumers’ adoption of innovative green products: Exploring green marketing strategies - Alharbi, Bandar Fahad M (Edelweiss Applied Science and Technology, 2025)
To examine how social and cultural factors influence consumer adoption of innovative green products in Saudi Arabia, the UAE, and Qatar while exploring the effectiveness of green marketing strategies and government initiatives in promoting sustainable consumption patterns. The study integrates multiple theoretical foundations: the Theory of Planned Behavior (TPB), the Innovation Diffusion Model (IDM), and the Green Marketing Mix (GMM). This integrated framework explains how cultural values, social norms, and environmental awareness interact with consumer behavior toward green products in the Gulf context. A mixed-methods approach was employed, combining quantitative surveys (N=847) with qualitative interviews (N=54). Data was collected through stratified random sampling across Saudi Arabia (n=421), the UAE (n=261), and Qatar (n=165). Structural equation modeling analyzed relationships between variables, while thematic analysis explored qualitative insights. Environmental consciousness emerged as the strongest predictor of green purchase intention (β = 0.36, p < 0.001), followed by perceived product quality (β = 0.28, p < 0.01). Cultural values showed significant influence, particularly in Saudi Arabia (M = 3.92) compared to the UAE (M = 3.65) and Qatar (M = 3.78). Qualitative findings revealed that religious principles and social norms significantly shape consumer behavior, while high costs remain a primary barrier to adoption. Organizations should develop culturally sensitive marketing strategies that align with Islamic environmental principles while addressing affordability concerns. Governments can enhance adoption through subsidies, improved distribution networks, and standardized certification systems. The findings provide a framework for implementing effective green marketing strategies in the Gulf region. This research uniquely combines cultural, social, and economic perspectives in examining green product adoption in the Gulf region. It provides novel insights into the interplay between religious values, social norms, and environmental consciousness in shaping sustainable consumption patterns. The study offers practical recommendations for policymakers and businesses to promote green consumerism while respecting cultural sensitivities.